The Contribution of Pluralistic Qualitative Approaches to Mixed Methods Evaluations. Issue 138 (6th June 2013) - Frost, Nollaig; Nolas, Sevasti‐Melissa
Abstract: There is a strong trend in policy‐making circles for strategic, systemic, and large‐scale interventions. Although such trends make sense in terms of economy of scale and scope, the political will necessary for making these large‐scale interventions a reality is often lacking, and the problem of the transferability of interventions from one local context to another (e.g., from trial conditions to local communities, and then across local communities) remains largely unsolved (Cartwright & Munro, 2010). © Wiley Periodicals, Inc., and the American Evaluation Association .